Pengaruh Efikasi Diri dan Praktek Lapangan Kependidikan terhadap Minat menjadi Guru - Taali Taali; Fathia Ulya Rinovsky (Jurnal Pendidikan Teknik Elektro, 2023)
This research was conducted with the aim of determining the effect of self-efficacy and educational field practice on interest in becoming a teacher for students of the 2018 and 2019 Electrical Engineering Education study program at Padang State University. The research method uses associative quantitative, this method expresses the effect between the independent variable and the dependent variable. All information analyzes based on multiple linear regression analytics. The population is active students from the Department of electrical engineering 2018 and. A total sample of 55 students has carried out PLK. Data collection using a questionnaire. With scoring using a Likert scale. The result of this research indicates that (1) Self-efficacy has a positive and significant effect on interest to become a teacher based on value tcount > ttable at the significance level of less than 5% (2) Educational Field Practice has a positive and significant effect on interest to become a teacher based on value tcount > ttable at the significance level of less than 5% (3) there is a mutually significant effect of self-efficacy and educational field practice on interest to become a teacher based on value Fcount > Ftable at the significance level of less than 5%.